2014
DOI: 10.1038/srep05575
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence quenching in gold - MoS2 hybrid nanoflakes

Abstract: Achieving tunability of two dimensional (2D) transition metal dichalcogenides (TMDs) functions calls for the introduction of hybrid 2D materials by means of localized interactions with zero dimensional (0D) materials. A metal-semiconductor interface, as in gold (Au) - molybdenum disulfide (MoS2), is of great interest from the standpoint of fundamental science as it constitutes an outstanding platform to investigate plasmonic-exciton interactions and charge transfer. The applied aspects of such systems introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
204
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(222 citation statements)
references
References 54 publications
18
204
0
Order By: Relevance
“…Moreover, it is well known that PL emission could be quenched when the emitter is in the close vicinity of the plasmonic resonator. 20 Moreover, Bhanu et al 21 have recently shown that the photoluminescence of MoS 2 flakes is strongly quenched upon Au deposition as a result of charge transfer from MoS 2 to Au. However, since in our experiments a PL enhancement of about 65% is measured ( Figure 3B), we can conclude that increased optical absorption into the MoS 2 overpasses the PL quenching.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is well known that PL emission could be quenched when the emitter is in the close vicinity of the plasmonic resonator. 20 Moreover, Bhanu et al 21 have recently shown that the photoluminescence of MoS 2 flakes is strongly quenched upon Au deposition as a result of charge transfer from MoS 2 to Au. However, since in our experiments a PL enhancement of about 65% is measured ( Figure 3B), we can conclude that increased optical absorption into the MoS 2 overpasses the PL quenching.…”
Section: Resultsmentioning
confidence: 99%
“…Auger recombination at WS 2 /Ti 3 C 2 T x interface is the first possible reason quenching the PL intensity of TT4. The PL intensity of MoS 2 can be greatly quenched at MoS 2 /graphene [32] and MoS 2 /Au [33] contact due to strong Auger recombination. The electric conductivity of Ti 3 C 2 T x is 4.2 × 10 −4 S/m [9], which is comparable to graphene.…”
Section: Optical Characterization Of Ws 2 /Ti 3 C 2 T X Mxenementioning
confidence: 99%
“…Remarkably, the 2D exciton emission is not spectrally shifted (within a few meV) compared to samples exfoliated onto SiO 2 /Si and the trion binding energy of E 2D-X0 PL À E 2D-XT PL % 31 meV is not influenced by the choice of metal substrate. Also, for the related ML material MoS 2 , it has been reported that the emission of the direct gap 2D excitons is little affected by the gold substrate, 41,42 presumably due to the very small exciton Bohr radius in ML TMDs. 43,44 The exact ratio of the PL intensities 2D-XT: 2D-X0 varies across the sample, compare in Fig.…”
mentioning
confidence: 99%